Perbandingan Hukum Pers Indonesia dan Thailand dalam Perspektif Hukum Tata Negara - Sari Febriyana Muriya; Erlina Erlina (Lembaga Yasin AlSys, 2026)
Freedom of the press is an important element in a democratic state, but its regulation and restriction differ in each country according to the constitutional character adopted. Indonesia and Thailand show fundamental differences in providing protection for freedom of the press, making it important to examine the relationship between a state’s constitutional character and the model of protection and restriction of press freedom. This study aims to analyze the comparison of press freedom regulation in Indonesia and Thailand from the perspective of constitutional law and to assess its conformity with the principles of the rule of law and human rights. This study is normative legal research using statutory, conceptual, and comparative approaches. Legal materials were collected through a literature study of laws and regulations, legal doctrines, and international human rights instruments, then analyzed juridically and comparatively. The results showed that Indonesia, as a state with the character of constitutional democracy, positions freedom of the press as a human right protected by the constitution through the 1945 Constitution of the Republic of Indonesia and Law Number 40 of 1999 concerning the Press, and is further strengthened by the existence of the Press Council as an independent institution. Conversely, Thailand, as a state characterized by constitutional monarchy, provides strong protection for the royal institution through Article 6 of the 2017 Constitution and Article 112 of the Thai Criminal Code, which restrict press freedom through the criminalization of criticism of the monarchy. Based on the principles of the rule of law, human rights, and General Comment No. 34 of the UN Human Rights Committee, Indonesia’s system of press freedom restrictions generally better fulfills the principles of legality, legitimate aim, and proportionality than Thailand’s system. The conclusion of this study affirms that the constitutional character of a state influences the level of protection and restriction of press freedom. These findings imply the importance of strengthening press regulations that are democratic, proportional, and human rights-oriented, as well as developing comparative constitutional law studies on the relationship between constitutional design and the protection of press freedom.